Using T-O-E theoretical framework to study the adoption of ERP solution - Hart O. Awa; Ojiabo Ukoha; Bartholomew C. Emecheta (Cogent Business & Management, 2016)
This paper provides further insight into IS adoption by investigating how 12 factors within the technology-organization-environment (T-O-E) framework explain SMEs' adoption of enterprise resource planning (ERP) software. Survey data were collected from executives of SMEs drawn from six fast service enterprises with strong operations in Port Harcourt, Nigeria. Purposive and snow ball sampling was adopted and the proposed framework was tested using the logistic regression; specifically, the likelihood ratios, Hosmer and Lemeshow's goodness of fit, and Nagelkerke R2 were used. The hypothesized relationships were supported at either p < 0.01 or 0.05 with each factor differing in its statistical coefficient and some bearing negative values; suggesting that some factors do not pose much threat to adopters but to non-adopters. Thus, adoption of ERP by SMEs is well-explained by T-O-E framework though it is more driven by technological factors than by organizational and environmental factors. Implicit is that the proposed model will be useful to IS vendors in making investment decisions and crafting marketing programs that appeal to non-adopters since they have more adoption challenges than adopters and to cause adopters to progress in the loyalty ladder.
Keywords: 650